Readdressing the Needs of Cancer Survivors During COVID-19: A Path Forward. (26th December 2020) - Jones, Jennifer M; Saeed, Hina; Katz, Matthew S; Lustberg, Maryam B; Forster, Victoria J; Nekhlyudov, Larissa
Abstract: The growing number of cancer survivors and the high prevalence of cancer-related physical and psychosocial effects pose important and pressing challenges to health systems. The coronavirus disease 2019 (COVID-19) pandemic has led to further stressors on cancer survivors and health care systems. As the pandemic continues to have substantial impact on the world, it is critical to focus attention on the health care needs of cancer survivors. In this commentary, we propose an adoption of essential steps that should be part of a continuous adaptive approach to promote effective cancer survivorship care during ongoing COVID-19 waves and beyond.